2018
DOI: 10.1590/1518-8345.2774.3085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serological markers for hepatitis and potential associated factors in patients with diabetes mellitus

Abstract: Objective:to estimate the prevalence of serological markers for hepatitis B and C in patients with diabetes mellitus and analyze potential associated factors. Method:a cross-sectional study with 255 patients with diabetes mellitus. Demographic, clinical, and risk behavior factors for hepatitis B and C were selected. The markers HBsAg, Anti-HBc IgG, Anti-HBc IgM, Anti-HBs, and Anti-HCV were investigated. A questionnaire and venous blood collection and inferential statistical analysis were used. Results:16.8% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
1
1
Order By: Relevance
“…The seroprevalence of 3.8% for HBsAg reported in this study is higher than those observed among diabetic patients in Italy (1.63%) [ 31 ], the Kurdistan Region of Iraq (2.13%) [ 32 ], and Ethiopia (3.7%) [ 33 ] but lower than those reported among diabetic patients in China (13.5%) [ 34 ] and Taiwan (13.54%) [ 35 ]. Moreover, the seroprevalence of 12.82% for HBcAb observed in this study is higher than that reported among diabetic patients in the United States (8.2%) [ 36 ] but lower than those reported among diabetic patients in Brazil (16.8%) [ 37 ] and China (62.3%) [ 34 ]. Differences in immunization status, risk factors, the burden of HBV infection in the general population, the levels of safety measures in public health centers, preventive strategies, and risk of exposure to HBV in different regions as well as differences in the sensitivity and specificity of diagnostic methods, study period, sociodemographic characteristics of the study population and number of participants in different studies might explain these variations in the seroprevalence of HBV infection in different parts of the world.…”
Section: Discussioncontrasting
confidence: 83%
“…The seroprevalence of 3.8% for HBsAg reported in this study is higher than those observed among diabetic patients in Italy (1.63%) [ 31 ], the Kurdistan Region of Iraq (2.13%) [ 32 ], and Ethiopia (3.7%) [ 33 ] but lower than those reported among diabetic patients in China (13.5%) [ 34 ] and Taiwan (13.54%) [ 35 ]. Moreover, the seroprevalence of 12.82% for HBcAb observed in this study is higher than that reported among diabetic patients in the United States (8.2%) [ 36 ] but lower than those reported among diabetic patients in Brazil (16.8%) [ 37 ] and China (62.3%) [ 34 ]. Differences in immunization status, risk factors, the burden of HBV infection in the general population, the levels of safety measures in public health centers, preventive strategies, and risk of exposure to HBV in different regions as well as differences in the sensitivity and specificity of diagnostic methods, study period, sociodemographic characteristics of the study population and number of participants in different studies might explain these variations in the seroprevalence of HBV infection in different parts of the world.…”
Section: Discussioncontrasting
confidence: 83%
“…Hepatitis B and C are more concentrated in the southern and southeastern regions, making their predominance in the white race; however, in more focused studies, especially those in the north and northeast, a higher number of cases can be observed in the brown and/or black race, which prevail in these regions. 3,[13][14][15] As for the age group, it is observed that people aged 30 to 39 years and 50 to 59 years had lower chances of presenting the Total Anti-HBc antigen. It is thus implied that people in the age group of 15 to 29 years have higher chances of presenting the Total Anti-HBc antigen.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies identify the Total Anti-HBc antigen more present in age groups from 30 to 39 years, contradicting the findings of this study. [15][16] This phenomenon is explained by the fact that the hepatitis B vaccine was introduced in the vaccination schedule only after 1998, making the age profile important in the investigation of cases with positive markers. 15 As for the presence of the Total Anti-HBc antigen and hepatitis B vaccination, it was observed that people who did not receive hepatitis B vaccination had a higher chance of presenting the antigen than those who were vaccinated, Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 diabetes mellitus has been associated with increased rates of infections [3] . Patients with T1DM are more vulnerable to HBV infection compared to the normal population [4] . It has been shown that T1DM had distinct effects on the immune system, involving both the humoral and cellular responses, which results in a less optimal reaction to vaccines compared to healthy controls [5,6] .…”
Section: Introductionmentioning
confidence: 99%